Synchronizing production planning and job scheduling: MILP models and exact algorithms - Mombelli, Aurélien; Quilliot, Alain (Journal of combinatorial optimization, 2025)
We address the synchronization of a resource production process with the consumption of related resources by jobs. Both processes interact through transfer transactions , which become the key components of the resulting scheduling problem. This Synchronized Resource Production/Job Processing problem ( SRPJP ) problem typically arises when the resource is a form of renewable energy (e.g., hydrogen, photovoltaic) stored in tanks or batteries. We first cast SRPJP into the Mixed-Integer Linear Programming (MILP) format and handle it through a branch-and-cut process involving specific No _ Antichain constraints derived from the structure of the feasible transfer transactions . Subsequently, we explore another approach, which involves eliminating non-binary decision variables and applying a Benders decomposition scheme. Finally, we reformulate the SRPJP problem as a path search problem, which we efficiently handle by designing a tailored adaptation of the A* algorithm.